MADRASAH DAN PERTUMBUHAN KEILMUAN DUNIA ISLAM: SEBUAH KAJIAN SOSIO-HISTORIS - Imam Solihin (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
This article was aimed at deeply discussing the development of madrasah and sciences in Islamic society from the socio-historical perspective. In the past, Islamic education was only implemented informally at homes, kuttab and mosque. In further development, after the Muslim community began to form, education was organized in a formal form, so that Islamic education later became one of the pillars of Islamic civilization. In this case, formal form of Islamic education is characterized by the emergence of madrasah as an educational institution and as well as an educational path. Inside the madrasah there is a pedagogical process of communication between educators of learners, from which it is expected to lead to the achievement of instructional goals. It can be said that historically the birth of a madrasah became a symbol of the awakening of the Islamic educational system. In the history of madrasah development in Indonesia, there are two types of madrasah, madrasah diniyah and non-diniyah madrasah. Madrasah diniyah is a religious education institution whose curriculum is 100% religious material. The non-diniyah madrasah is a religious education institution whose curriculum, in addition to religious material, covers a general subject with a diverse percentage.